Better living through understanding the insula: Why subregions can make all the difference. (15th October 2021) - Centanni, Samuel W.; Janes, Amy C.; Haggerty, David L.; Atwood, Brady; Hopf, Frederic W.
Abstract: Insula function is considered critical for many motivated behaviors, with proposed functions ranging from attention, behavioral control, emotional regulation, goal-directed and aversion-resistant responding. Further, the insula is implicated in many neuropsychiatric conditions including substance abuse. More recently, multiple insula subregions have been distinguished based on anatomy, connectivity, and functional contributions. Generally, posterior insula is thought to encode more somatosensory inputs, which integrate with limbic/emotional information in middle insula, that in turn integrate with cognitive processes in anterior insula. Together, these regions provide rapid interoceptive information about the current or predicted situation, facilitating autonomic recruitment and quick, flexible action. Here, we seek to create a robust foundation from which to understand potential subregion differences, and provide direction for future studies. We address subregion differences across humans and rodents, so that the latter's mechanistic interventions can best mesh with clinical relevance of human conditions. We first consider the insula's suggested roles in humans, then compare subregional studies, and finally describe rodent work. One primary goal is to encourage precision in describing insula subregions, since imprecision (e.g. including both posterior and anterior studies when describing insula work) does a disservice to a larger understanding of insula contributions. Additionally, we note that specific task details can greatly impact recruitment of various subregions, requiring care and nuance in design and interpretation of studies. Nonetheless, the central ethological importance of the insula makes continued research to uncover mechanistic, mood, and behavioral contributions of paramount importance and interest. This article is part of the special Issue on 'Neurocircuitry Modulating Drug and Alcohol Abuse'. Highlights: Insula is critical for many motivated behaviors, with subregions interesting but still poorly understood. Insula regulates numerous functions, including, interoception, emotion, addiction, and other neuropsychiatric conditions. Generally, posterior, mid, and anterior insula are linked to somatosensory, limbic/emotional, and cognitive integration. We extensively review human and rodent findings, noting potential behavioral patterns for insular subregions. This review is meant to guide formulation of future work to give critical mechanistic insights and dissociations.